Acute Vision Loss Following Endoscopic Sinus Surgery - Serena Byrd; Adnan S. Hussaini; Jastin Antisdel (Case Reports in Otolaryngology)
A 41-year-old female with a history of uterine cancer and Celiac and Raynaud’s Disease presented to our institution with frequent migraines and nasal congestion. She underwent functional endoscopic sinus surgery (FESS) and experienced acute unilateral vision loss postoperatively. Rapid recognition of the etiology and effective treatment are paramount given the permanent and irreversible vision loss that can result. Arterial vasospasm following FESS is rare. Patients with autoimmune diseases have perhaps an increased risk for vasospasm secondary to an increased vasoreactive profile. We present the first documented case of nitroglycerin sublingual therapy to successfully treat ophthalmic artery vasospasm following FESS. Nitroglycerin sublingual therapy is a promising treatment for ophthalmic vasospasm secondary to its ability to cross the blood-ocular barrier, its rapid onset of action, and its ability to promote relaxation of vascular smooth muscle.